Analysis of the marginal adaptation of temporary filling materials to tooth tissues - A. V. Makonin; I. S. Kopetskiy; I. A. Nikolskaya; L. V. Pobozhieva; J. V. Shevelyuk; A. A. Khritova; I. A. Shalaev (LLC "Endo Press", 2022)
Aim. To evaluate the marginal fit of temporary filling materials used in practice of a dentist-therapist.Materials and methods. The analysis of the degree of marginal fit of temporary sealing materials was carried out: light polymerization-«Tempofot liquid-flowing» (VladMiVa), «Restorin liquid-flowing (Technodent)», «Tempofot packable» (VladMiVa) and chemical curing - «Parasept» (VladMiVa), «Dentin paste» (Vladmiva), «Tempodent» (Technodent). The study was conducted on 120 removed teeth.Results. After 1 day of exposure, the materials «Dentin paste», «Tempodent» and «Tempofot packable» were penetrated by the hyposalix solution along the filling-tooth border. It can be stated that these materials have no hermetic properties. Thematerial «Parasept» and the materials «Tempofot liquid-flowing», «Restorin liquid-flowing» retained their hermetic properties, there was no staining of the filling-wall border of the tooth. After 3 days, the materials «Parasept» and «Tempofot liquid-flowing» staining was not detected, the material «Restorin liquid-flowing», the penetration of the dye to the mouth of the root canals was noted.Conclusions. The study found that temporary sealing materials of chemical and light polymerization have various hermetic properties.